Respuesta :

ANSWER

The solution is (1,-3)

EXPLANATION

The system of Equations are;

[tex]x=4+y[/tex]

and

[tex]-10x+6y=-28[/tex]

We substitute the first equation into the second equation to get:

[tex]-10(4 + y)+6y=-28[/tex]

We expand the parenthesis to get:

[tex]-40 - 10y+6y=-28[/tex]

Group similar terms to get:

[tex]- 10y+6y=-28 + 40[/tex]

Simplify the similar terms to get;

[tex] - 4y = 12[/tex]

Divide both sides -4.

[tex]y = \frac{12}{ - 4} [/tex]

[tex]y = - 3[/tex]

We put y=-3 into the first equation to get:

[tex]x = 4 + - 3 = 1[/tex]

Therefore the solution is (1,-3)